The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1111/1541-4337.12840
|View full text |Cite
|
Sign up to set email alerts
|

Alginate‐based delivery systems for food bioactive ingredients: An overview of recent advances and future trends

Abstract: Due to its advantagessuch as ionic crosslinking, pH responsiveness, excellent biocompatibility, biodegradability and low price, alginate has become one of the most important natural polysaccharides extensively used in constructing desired delivery systems for food bioactive ingredients. In this review, the fundamental knowledge of alginate as a building block for construction of nutraceutical delivery systems is introduced. Then, various types of alginate-based nutraceutical delivery systems are classified and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(63 citation statements)
references
References 116 publications
(202 reference statements)
0
63
0
Order By: Relevance
“…Alginate also exhibits mucoadhesive properties and, in contrast to chitosan, it is also water-soluble. In addition, studies have shown that alginate-based substances are pH-sensitive, being a useful tool for controlling the release of encapsulated biomolecules [26,47,[52][53][54]. Alginate is a promising candidate material for the oral, ocular, nasal, parenteral, and mucosal drug delivery of various moieties, including nucleic acids, drugs, and vaccine formulations [55][56][57][58][59].…”
Section: Individual and Synergic Propertiesmentioning
confidence: 99%
“…Alginate also exhibits mucoadhesive properties and, in contrast to chitosan, it is also water-soluble. In addition, studies have shown that alginate-based substances are pH-sensitive, being a useful tool for controlling the release of encapsulated biomolecules [26,47,[52][53][54]. Alginate is a promising candidate material for the oral, ocular, nasal, parenteral, and mucosal drug delivery of various moieties, including nucleic acids, drugs, and vaccine formulations [55][56][57][58][59].…”
Section: Individual and Synergic Propertiesmentioning
confidence: 99%
“…Alginate has been approved by the FDA as a material generally recognized as safe (GRAS) without special restrictions. Since the 1980s, the applications of alginate have rapidly expanded in food, chemical, printing, agriculture and medicine [24,[30][31][32]. Alginic acid is insoluble in water, however the sodium alginate forms after binding Na+ can be completely dissolved in water.…”
Section: Structure Properties and Historymentioning
confidence: 99%
“…Alginate has been approved by the FDA as a material generally recognized as safe (GRAS) without special restrictions. Since the 1980s, the applications of alginate have rapidly expanded in food, chemical, printing, agriculture and medicine [ 24 , 30 , 31 , 32 ].…”
Section: Alginate Hydrogelsmentioning
confidence: 99%
“…Alternatively, sodium alginate is a polysaccharide commonly used to formulate edible coatings because of its biodegradability, biocompatibility, low toxicity, and film-forming properties [ 47 ], which exhibit great value in storage. A recent study showed that loading potential probiotic fruit-derived lactic acid bacteria (LAB) strains into sodium alginate (SA) coating could effectively reduce the anthracnose lesion development in guava and mango contaminated with either of the tested Colletotrichum strains during storage [ 41 ], which can significantly improve the overall postharvest quality and long storage resistance of fruits [ 41 ].…”
Section: Alginate-based Probiotics Deliverymentioning
confidence: 99%